Preparation and dielectric properties of silver@poly(vinyl pyrrolidone)/poly(vinylidene fluoride) composites. (1st November 2016) - Li, Hairong; Yang, Jinhui; Fang, Dong; Liu, Lei; Chen, Jianping; Jiang, Ming; Xiong, Chuanxi
Abstract : Silver@poly(vinyl pyrrolidone) (Ag@PVP) core–shell nanoparticles are synthesised via a one‐step method. Ag@PVP/poly(vinylidene fluoride) (PVDF) composites with desirable dielectric properties were reported. It was found that the dielectric losses for Ag@PVP/PVDF composites were rather low similar to that of pure PVDF because of the insulating PVP coating. The Ag@PVP/PVDF with PVP of lower molecular weights exhibited more desirable dielectric properties than those with PVP of higher molecular weights. PVP can offer interesting permittivity enhancements without significantly adversely affecting the dielectric losses of the PVDF matrix. The results of this work make it possible to obtain the percolative composites with low dielectric loss and high permittivity by using Ag@PVP through simple methods.